دراسة تحسين السعة في نظام GSM - عباس حسن; محمد ناجي (Latakia University Journal -Engineering Sciences Series, 2019)
يهدف هذا البحث إلى تحسين السعة في نظام خلوي بهدف الوصول إلى نظام يلبي حاجات المستخدمين المتزايدة. وقد تم اعتبار الحركة تتوزع في المنطقة المدروسة بشكل منتظم. وتم إجراء مقارنة فقد المسار في حال استخدام نمط Hata Okumura وف يحال الفراغ الحر. ومن ثم دراسة تقديرات التغطية ومفهوم المنطقة الفعالة واحتمالية كون مستوى الإشارة أكبر من مستوى العتبة وعلى أساس القيم المفروضة يتم حساب نصف قطر الخلية. ومن ثم دراسة حمل الحركة في موقعي خليتين في منطقة معينة وحساب حمل الحركة التي تقدمها الخلية وحمل الحركة ساعة المشغولية ومقدار الزيادة في السعة التي تقدمها الخلية من خلال إضافة ترددات إلى موقع الخلية. كما تم استخدام MATLAB 6.1 في إجراء بعض الحسابات وتوضيح العلاقات. This research aims to improve the capacity in a cellular system to obtain a system which satisfies the increased user’s needs. We considered that the traffic distributes uniformly in the studied region. In addition to, we compared the free space path loss model with Okumura-Hata model, and studied the coverage estimation, area reliability, the probability of being the signal level above the threshold level, and we calculated the cell radius depending on the virtual values. We studied the traffic load in two cell sits, and evaluated the traffic load that a cel can support, the amount of traffic in busy hour, and the capacity increase by adding new frequencies to the cell sits. At last we used Matlab 6.1 to achieve many calculations and to illustrate the relations.